Disruption of the eEF1A1/ARID3A/PKC‐δ Complex by Neferine Inhibits Macrophage Glycolytic Reprogramming in Atherosclerosis - Baoping Xie; Li‐Wen Tian; Chenxu Liu; Jiahua Li; Xiaoyu Tian; Rong Zhang; Fan Zhang; Zhongqiu Liu; Yuanyuan Cheng (Advanced Science)
Abstract Glycolytic reprogramming of macrophages is a decisive factor in atherosclerosis (AS) plaque formation. Eukaryotic elongation factor 1A1 (eEF1A1) plays an important role in protein synthesis, ubiquitination degradation, and nuclear translocation. However, the potential function of eEF1A1 in AS has not yet been fully understood. Here, the natural small molecule neferine (Nef), which targets eEF1A1 to suppress macrophage glycolytic reprogramming is discovered. In this work, chemical genetics and non‐modified target confirmation assays are used to confirm that eEF1A1 is a direct target of Nef. Mechanically, Nef disrupted the formation of the eEF1A1/ARID3A/PKC‐δ complex, inhibits phosphorylation of ARID3A at Thr491, and consequently prevents its nuclear translocation. Meanwhile, it is verified that ARID3A is a transcriptional regulator of enolase 2 (ENO2), an important enzyme in the glycolytic process. Nef suppresses ENO2 transcription activation by affecting ARID3A binding to the promoter region of ENO2, which results in macrophage glycolytic reprogramming inhibition and transformation of macrophages from M1 to M2. Collectively, these findings provide an attractive future direction for AS therapy by inhibiting ARID3A/ENO2‐mediated macrophage glycolytic reprogramming by targeting eEF1A1.